Synchronisation using wireless trigger-broadcast for impedance spectroscopy of battery cells - Roscher, Valentin; Schneider, Matthias; Durdaut, Phillip; Sassano, Nico; Pereguda, Sergej; Mense, Eike; Riemschneider, Karl-Ragmar (2015 IEEE Sensors Applications Symposium (SAS), 2015)
In electric vehicles, batteries with many cells are used to supply the high voltages needed for the power train. The battery is controlled by a battery management system (BMS) which needs measurement data from each individual cell. Up to now, wired solutions with specialized measurement controllers for battery modules are in use. Some of these communicate over data bus structures. Our group proposes as an alternative solution the use of wireless communication in the near RF field area. The basics of this solutions have already been published [1]. In this article we present more advanced functionality for the wireless sensors approach. A functional module has been developed for impedance spectroscopy of each individual cell in the battery stack during automotive operation. Electrochemical impedance spectroscopy is a powerful method to determine the battery state beyond common and simple models. This technique needs precise and synchronized measurements of the common current and the voltages of the individual cells. A communication and control protocol has been implemented in hard- and software, including a trigger-broadcast operating mode. This solution has to fulfill the time precision requirements of the distributed measurements in the range of a few μs. Therefore, proprietary protocol solutions have been developed. Additional modules in the sensor system allow other functions such as cell balancing and an energy saving wake-up function for the sensor modules. These sensor modules are designed as tailored hardware for integration inside the individual battery cells.